Rapid and precise identification of cervicothoracic necrotizing fasciitis caused by Prevotella and Streptococcus constellatus by using Nanopore sequencing technology: a case report - Zhao, Manna; Leng, Xuejun; Xu, Jie; Cui, Juanjuan; Li, Shuo; Zhao, Weifeng (Frontiers in Medicine, 2024)
Introduction Cervicothoracic necrotizing fasciitis (CNF) is one form of necrotizing soft-tissue infections, which could lead to patient demise during short course. Therefore, early recognition and immediate treatment contribute to promising prognosis of patients. Case presentation A 58-year-old diabetic patient presented with a sore throat and progressive irritation of the neck and chest for 4 days. The initial diagnosis was considered to be soft-tissue infection and the clinician gave empirical anti-infectious medication for expectant treatment. During the course of disease, surgical incision was performed to relieve suffocation and shortness of breath. The drainage fluids were detected with microbiological culture and molecular sequencing. Nanopore sequencing technology (NST) helped to identify the coinfection of Streptococcus constellatus and Prevotella spp., which was not recognized during the original period of 15 days. The precise identification of pathogen supported to guide the pharmacologic treatment with meropenem and linezolid. Ultimately, combined with the surgical observation and post-surgical pathological examination, the patient was diagnosed as CNF, which could be much more acute and serious than normal soft-tissue infections. The patient has been successfully treated with prompt antimicrobial medication and appropriate surgical debridement. Conclusion This case presented a CNF patient with type 2 diabetes, successfully recovered after prompt microbial detection, precise anti-infectious treatment, and appropriate surgical intervention. It highlights the importance of recognizing pathogen by applying rapid microbiological detection, including NST, in acute and serious infectious disease.